2010
DOI: 10.1124/jpet.110.169284
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Insulin-Producing Cells Derived from Endometrial Mesenchymal Stem-like Cells

Abstract: Studies have demonstrated that mesenchymal stem-like cells can be isolated from endometrium. However, the potential of endometrial-derived stem cells to differentiate into insulin-positive cells and functionally secrete insulin remains undetermined. We isolated endometrial mesenchymal stem-like cells (EMSCs) from human endometrial tissue from six donors. The insulin-secreting function of EMSCs was further analyzed in vitro and in transplanted grafts in vivo. We successfully isolated EMSCs from human endometriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 32 publications
3
40
0
1
Order By: Relevance
“…Likewise, endometrial stem cells can be pushed down a pathway toward insulin production in culture and transplantation experiments using the modified insulin producing cells continued to produce insulin in vivo and regulated blood glucose levels in diabetic mice [38]. In similar studies, Li et al [39] and Hida et al [40] reported transdifferentiation of human endometrial mesenchymal stem-like cells into insulin-producing cells and human menstrual blood-derived mesenchymal cells into cardiac precursor-like cells, respectively, which, when xenotransplanted into diseased mouse models, helped restore tissue function. These results along with our own demonstrate the plasticity of endometrial mesenchymal cells, as well as their potential use in regenerative medicine.…”
Section: Figmentioning
confidence: 96%
“…Likewise, endometrial stem cells can be pushed down a pathway toward insulin production in culture and transplantation experiments using the modified insulin producing cells continued to produce insulin in vivo and regulated blood glucose levels in diabetic mice [38]. In similar studies, Li et al [39] and Hida et al [40] reported transdifferentiation of human endometrial mesenchymal stem-like cells into insulin-producing cells and human menstrual blood-derived mesenchymal cells into cardiac precursor-like cells, respectively, which, when xenotransplanted into diseased mouse models, helped restore tissue function. These results along with our own demonstrate the plasticity of endometrial mesenchymal cells, as well as their potential use in regenerative medicine.…”
Section: Figmentioning
confidence: 96%
“…MenSCs transferred dystrophin into dystrophied myocytes through cell fusion and transdifferentiation in vitro and in vivo Toyoda et al, 2007). Furthermore, stem cells isolated from endometrium have been proven to be an excellent cell source for treating experimental disease models, such as critical limb ischemia, stroke, type I diabetes mellitus, Parkinson's disease, and other neurodegenerative disorders (Murphy et al, 2008;Borlongan et al, 2010;Li H.Y. et al, 2010;Sanberg et al, 2011;Santamaria et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo assessments of transplanting menstrual blood-derived stem cells reveal their effi cacy and safety in stroke. They are a potential cell source for treating other CNS disorders [13]. Use in diabetes to prolong graft tissue survival is being considered [14].…”
Section: Othersmentioning
confidence: 99%